Effective budgeting for business - Video Education Australasia (Australia : Video Education Australasia, 2007)
This program explores the methods in which a number of businesses prepare budgets for cash, profit and position. More importantly it examines the use of budgeted information to create opportunities for success in the future
Title from title screen
Executive producer, Simon Garner ; camera, Max Davis
Voice over: Amanda Brocklebank
DVD format
Keywords: Budget in business; Business forecasting